Reka Bentuk Sistem Penuaian Air Hujan Pelbagai Fungsi Terhadap Rumah Lot Banglo - Miswan, Rasyidah; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun; Kassim, Narimah; Zainal, Rozlin (Research in Management of Technology and Business, 2021)
Currently, every new residential building such as bungalows and semi-detached houses with a roof area equivalent to or more than 100 square meters has been required to install SPAH. SPAH is a technology used to collect and store rainwater from the roof for reuse with various functions and purposes. SPAH installation is not only focused on homes but it can also be applied to the domestic, agricultural and industrial sectors. The problem of this study is the lack of installation of rainwater harvesting system on bungalow lot houses as well as rainwater catchment is not used more efficiently, causing waste. Therefore, the objective of the study was to identify the various functions of SPAH for a bungalow lot house as well as to propose a suitable 3D design drawing using Revit and Lumion construction software for rainwater harvesting system (SPAH) specifically for a bungalow lot house. The method used to achieve the objectives of this study is through quantitative methods that is, questionnaires prepared and distributed to 30 respondents consisting of bungalow lot owners and using rainwater harvesting system. This study was conducted in Sitiawan, Perak Darul Ridzuan and this design was made to provide views and suggest  ideas to housing developers to design a multi-functional SPAH in its overall use thus attracting the community to install this system in their homes, among the functions proposed by the designer is outdoor use such as landscaping, building cooling, car washing, floor washing, windows and indoor use of the house including washing machine, shower tank There are many benefits and advantages if SPAH is applied to every house, among them can save water bills, reduce the temperature in the house and so on.